Medical negligence law in Malaysia (Revised edition) - Jahn Kassim, Puteri Nemie (International Law Book Services, 2008)
The most important ironies of modern healthcare is that public expectations are rising faster than the ability of health services to meet them. Patients nowadays no longer want to be treated as passive recipients of medical care. Instead, they want to be treated as co-producers or partners able to manage their illnesses. The aim of producing the Revised Edition of Medical Negligence Law in Malaysia is to highlight the new medical negligence cases and examine the changes for future reform. This revised edition also has a chapter on the Islamic perspective on medical negligence.